Quality and accuracy of cardiopulmonary resuscitation teaching in short videos: an analysis across three major short video platforms - Xinyue Xie; Yaoyun Li; Zhiqiao Chen; Peiyang Zhou; Xiaoqing Jin (BMC Medical Education)
Abstract Objective Cardiopulmonary resuscitation (CPR) is vital for saving patients experiencing cardiac arrest. Teaching CPR skills through short videos offers numerous advantages. However, potential inaccuracies or misinformation could mislead the public and impact the effectiveness of CPR education. This study aims to evaluate the quality and accuracy of CPR instructional videos shared on three major short video platforms in China (TikTok, Bilibili, and REDnote), analyze common irregular or erroneous practices, and provide valuable suggestions for content optimization. Methods The collected videos were evaluated using a five-point scoring criterion based on 2020 American Heart Association (AHA) Guidelines for Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC). The videos were categorized into three levels: excellent, moderate, and poor, based on their video quality scores for CPR procedures and non-procedural content. Further categorization was made by video duration (≤5 min as short; >5 min as long). Additionally, the most critical and prevalent irregularities or errors were documented, and a detailed analysis of the most popular video from each platform was carried out. The relationship between video quality and popularity, and video duration and popularity were examined separately. Results A total of 100 CPR instructional videos were analyzed. While 86% of the videos were produced by healthcare professionals, substantial errors were identified in critical areas such as the extra time spent removing foreign body airway obstruction (67%), and incorrect hand position during compression (62%). Other issues with non-procedural content were identified, including video acceleration (13%), lack of step-by-step explanations (61%), etc. Statistical analysis revealed no significant differences in popularity across videos of different quality or duration (p = 0.876 among video quality groups for CPR procedures, p = 0.988 among video quality groups for non-procedural content, p = 0.260 between video duration groups). Conclusions This study identified the necessity for improvements in CPR procedures and non-procedural content of CPR instructional videos. To enhance video quality, measures such as rigorous review mechanisms, public feedback and promotion of certified high-quality videos are recommended.